EFFECTIVE CLEANER OF RAW COTTON FROM SMALL WEEDS - Abdullaeva, Dona Toshmatovna (Educational Research in Universal Sciences, 2023)
The article under discussion investigates the questions of rational and economic expediency in cleaning and storage of highly clogged and wet raw cotton of manual and machine picking. The purpose of the article is to consider proposals for design changes in new machines proposed by the authors, aimed at increasing their productivity and improving the quality of cotton fiber during cotton ginning. The authors of the article determined the reasons of raw cotton selfheating in bunches and covered storages, besides the process of raw cotton overheating with the help of centrifugal fan during transportation by suction pipeline has been studied as well.